KNOWLEDGE TO PRACTICE: ENHANCING POSYANDU CADRES’ COMPETENCE IN METABOLIC SYNDROME SCREENING AND EDUCATION - Puspasari, Anggelia; Maharani, Citra; Syauqy, Ahmad; Fitri, Amelia Dwi; Shafira, Nyimas Natasha Ayu; Enis, Rina Nofri; Kusdiyah, Erny; Delfira, Annissa; Hasmita, Debby; Amatullah, Afifah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Metabolic syndrome (MS) is a growing public health problem, characterized by central obesity, high blood sugar levels, increased blood pressure, and lipid profile disorders that can increase the risk of cardiovascular disease. This community service activity was carried out to strengthen the competence of Posyandu cadres in the Tahtul Yaman Community Health Center (Puskesmas) work area in Jambi City in conducting early detection and providing education about MS. The program was implemented through three main stages: module development, module-based training, and direct mentoring in the field. The training module was designed by integrating the Health Belief Model (HBM) approach and andragogy principles, so that the learning process was more participatory and oriented towards the cadres' real-life experiences. A total of 15 cadres from nine Posyandus actively participated in this activity. Evaluation was carried out through pre- and post-tests to assess knowledge gains, and the Direct Observation of Procedural Skills (DOPS) method to measure practical skills. The results showed a significant increase in knowledge scores, with the pass rate increasing from 73.33% to 100% after the training. Cadres were able to implement screening procedures according to standards and explain the examination results well. However, the communication-education aspect still needs strengthening to make health messages more easily accepted by the public. Overall, this program has proven effective in increasing the capacity of Posyandu cadres as the frontline of promotive and preventive health services at the community level.